Some Results on Real Valued Continuous Functions on an Interval (European Journal of Pure and Applied Mathematics, 2017)
In this paper, results mainly on the structures of some special classof real valued functions on an interval are discussed. Two other signicantresults are also established. These results have been derived and presentedmainly in the perspective of study of relations between real valued functionsand their derivatives. The results are very fundamental in nature and may beuseful in the next course of generalizations or improvements in this direction.